Focus on Minotaure : The Animal-Headed Review. - Musée Rath, Genève; Musée d'art Moderne de la ville de Paris Paris (Geneva : Musée d'Art et d'Histoire, 1987)
Alvarez Bravo, Manuel ; Arp, Hans ; Balthus ; Beaudin, André ; Bellmer, Hans ; Borès, Francisco ; Brancusi, Constantin ; Braque, Georges ; Brassaï ; Brauner, Victor ; Breton, André ; Breton, Jacqueline ; Brignoni, Serge ; Brunius, Jacques B. ; de Chirico, Giorgio ; Cornell, Joseph ; Dali, Salvador ; Delvaux, Paul ; Derain, André ; Dominguez, Oscar ; Duchamp, Marcel ; Ernst, Max ; etc.
Focus on Minotaure : The Animal-Headed Review, Musée Rath, Geneva, 17 October 1987 - 31 January 1988 / Musée d'Art Moderne de la Ville de Paris, 17 March - 29 May 1988
boek